Inside Women's Representative General Election - Awis Alhkarni; Wendra Yunaldi; Erry Gusman (Advances In Social Humanities Research, 2023)
Talking about women's rights in politics and democracy in Indonesia, it has actually been around for a long time since Indonesia became independent through the provisions of Article 27 paragraph (1) of the 1945 Constitution which stipulates that, "All citizens have the same position in law and government and are obliged to uphold the law and that government with no exception " . Women in various parts of regencies / cities in Indonesia strive to fight for their political rights. The concept of women's representation as candidates for DPRD members using affirmative action in the form of a 30% female quota. Law Number 7 of 2017 concerning General Elections still takes into account the city that 30% female representation is the requirement to become a candidate for political party election participants by "including at least 30% (thirty percent ) of women's representation in the management of central political parties". In conducting research, the author uses the Juridical Empirical research method, namely a research method also known as field research (Field Research) is a collection of material or research material that must be hunted or hunted by yourself because it is not yet available. Then carried out to the political party faction that sits in the DPRD of the city of Bukittinggi , the General Election Commission and the General Election Supervisory Body of the City of Bukittinggi . With the aim of knowing the concept of women's representation, the obstacles of political parties in the nomination of women's representation and efforts to support the affirmative action concept of women's representation in the Bukittnggi City DPRD . From the research results in the form of interviews, it can be concluded that the lack of support for women affects the quality of women's work in parliament; and the existence of local cultural factors (Minangkabau) is the main obstacle to achieving women's representation in parliament. With efforts to increase awareness of election laws and regulations in order to understand statutory provisions; and understand the sensitivity to issues developing in society and can facilitate problems occurring